Elimination of Abnormal Time-Delay in Phase-Shift-Based PWM for Five-Level Hybrid Active NPC Inverters - Hakami, Samer Saleh; Lee, Kyo Beum (ICPE 2023-ECCE Asia - 11th International Conference on Power Electronics - ECCE Asia: Green World with Power Electronics, 2023)
Five-level hybrid active neutral-point-clamped (NPC) inverters have recently attracted much attention due to their high power density and quality, dv/dt, and low stress on switching devices. There have been various modulation schemes presented to control the five-level hybrid active NPC inverter. Among these approaches is phase-shift pulse-width-modulation (PWM), which has a natural voltage balancing capability. However, implementing this scheme on a microcontroller is complex and results in a distortion in the output voltages owing to an abnormal delay in the generated PWM pulses. Therefore, an effective switching scheme is proposed in this paper to eliminate any abnormal delay in the conventional phase-shift PWM. The proposed switching scheme is generated based on inverted reference voltages per phase to control the five-level hybrid active NPC inverter. Simulation and experimental results are provided to verify the effectiveness of the proposed phase-shift PWM in generating five-level output voltage without any distortion.
Keywords: Active neutral point clamped; Five-level hybrid active neutral-point-clamped inverter; In-phase; Neutral-point clamped inverters; Output voltages; Phase-shift pulse width modulations; Phase-shift pulse-width-modulation; Pulsewidth modulations (PWM); Switching scheme; Time-delays; Five-level hybrid active neutral-point-clamped (NPC) inverters; microcontroller; phase-shift pulse-width-modulation (PWM); time-delay